Transcriptome sequencing reveals jasmonate playing a key role in ALA-induced osmotic stress tolerance in strawberry - Yan Zhong; Xin Wei; Jianting Zhang; Liangju Wang (BMC Plant Biology)
Abstract Background Strawberry (Fragaria × annanasa Duch.) is an important economic fruit worldwide, whose growth and development are often hindered by water deficiency. 5-Aminolevulinic acid (ALA), a natural plant growth regulator, has been suggested to mitigate the osmotic damages by promoting root water absorption, osmotic adjustment, photosynthetic capacity, and antioxidant improvement. However, the regulatory mechanism remains unclear. Results In the current study, the underlying mechanism by determination of various physiological indices, as well as transcriptome sequencing and the weighted gene correlation network analysis (WGCNA) of 10 mg L− 1 ALA treated strawberry leaves and roots stressed by 20% polyethylene glycol 6000 (PEG) treatment. The findings indicated that ALA enhanced osmotic stress tolerance reflected by enhancing relative water content (RWC), root development, gas exchange parameters and antioxidant enzyme activities, and decreasing the leaf H2O2 and malondialdehyde (MDA) content. Transcriptome analysis showed that the differentially expressed genes (DEGs) stimulated by exogenous ALA were mostly associated with the secondary biosynthesis and hormones signaling pathways, especially jasmonates (JAs). The JA derivative (+)-7-iso-jasmonoyl-L-isoleucine (JA-Ile) was found to be elevated in the strawberry leaves and roots treated with ALA under PEG stress. Additionally, exogenous methyl jasmonate (MeJA) alleviated osmotic stress damages similarly to ALA, while its synthesis inhibitor diethyldithiocarbamate (DIECA) led to adverse effects on strawberries, which can be relieved by further additional application of ALA. Conclusions Theses findings suggest that JAs can act as the necessary signaling molecules involved in ALA-improved osmotic stress tolerance networks. This provides a new insight for further study on how ALA can help plants cope with water stress.